Cut-Paste-Repeat? The maintenance of authoritarian pedagogies through tertiary dance education in China. Issue 4 (4th November 2020) - Rowe, Nicholas; Xiong, Xi
Abstract : Tertiary dance programmes in China are undergoing significant changes, as graduate attributes are reconfigured to address key employment needs of 21st century knowledge economies. This transformation is challenged by an entrenched culture of authoritarian teaching practices, which maintains former ways of knowing and doing. While this dilemma has been recognized within scholarship in China, the complexity of authoritarian teaching pedagogy, and what sustains it, requires further unpacking for such a transformation to be effective. Through a qualitative enquiry gathering the narratives of dance teachers at tertiary institutions across China, this article investigates how current dance teachers experienced and maintain authoritarian pedagogical practices, and promote these practices to future dance educators.